Biology and Management of Long-Stalked Phyllanthus in Ornamental Crop Production - Theresa Chormanski; Chris Marble; Lyn Gettys (EDIS)
This 5-page fact sheet discusses the characteristics of long-stalked phyllanthus and explains how to control its growth in a nursery environment. Written by Theresa Chormanski, Chris Marble, and Lyn Gettys, and published by the UF Department of Environmental Horticulture, April 2015.